Concepts for immunotherapies in gliomas - Platten, Michael; Reardon, David A. (Seminars in neurology, 2018)
Strategies to empower the immune system to successfully attack cancers, including vaccination approaches, adaptive T cell therapies, and immune checkpoint modulators, have recently achieved remarkable success across a spectrum of cancer indications. Nonetheless, with rare exception, only a minority of patients with a given type of cancer respond to an immunotherapeutic when administered as single-agent therapy. Although under extensive laboratory and clinical investigation, the role of these approaches for glioma patients remains to be determined. While the central nervous system (CNS) is no longer regarded as an immunoprivileged sanctuary, nuances regarding immune responses in the CNS may impact on the activity of immunotherapy treatments of brain tumor patients. Furthermore, many common CNS tumors such as World Health Organization grade III and IV (high grade) gliomas utilize myriad, nonoverlapping strategies to dampen or extinguish antitumor immune responses. For these reasons, critical research efforts are focused on identifying biomarkers that predict patients with a heightened likelihood of therapeutic benefit as well as evaluating rationally designed combinatorial immunotherapy approaches with potentially complementary mechanisms of immune-activation for brain cancer patients.
Gesehen am 04.05.2020